Research as accompaniment
1 online resource
Keywords: "This volume expands conversations about participatory, community-engaged, and action-oriented research that inspires social change. The authors contend that long-term community partnerships, inspired by solidarity and characterized by equality and reciprocity, result in a deep understanding of community concerns and increase the likelihood that research findings will have an impact on both the community partners and the broader society. Such research relationships, the authors maintain, are best understood as accompaniment. This book recognizes the potential as well as constraints of conceptualizing research as accompaniment and emphasizes that this approach is both a continuum and a process. Suitable for students and scholars of ethnographic and qualitative methods (and professionals using those methods, such as those in NGOs). It will appeal to those interested in research with communities in a wide variety of social science and other disciplines including Anthropology, Nursing, and Public Health amongst others"--